Indigeneity and Development in Botswana: The Case of the San in the Central Kalahari Game Reserve - Woof, Jonathan (Université d'Ottawa | University of Ottawa, 2014)
This paper discusses how San involved with the Central Kalahari Game Reserve (CKGR) in Botswana express and interpret their sense of indigeneity amidst the systemic marginalization and discrimination that they have experienced. By looking in depth at the case in the CKGR, the nature of prominent San CSOs and impact of the ‘Global North,’ this paper finds that San affirm their sense of indigeneity by critiquing the post-colonial development discourse, attempting to restore their land rights in the CKGR and by implementing ‘life-projects’ which affirm their ontologies and traditions. The findings of the paper suggest that the concept of indigeneity is diverse and complex and may not be as liberating as its proponents hope.